Mineral Status of the Far East (9156413b-c9e4-4175-8cda-c56f59239f7a) - Kung-Ping Wang (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1951)
This is the second installment of two-part article on the Far East. The mineral situation in Hong Kong, Indo-China, Thailand, Burma, Malaya, Indonesia, the Philippines, and British Borneo is covered.